Language and HIV communication - Lynn VA (Dove Medical Press, 2017)
Vickie A LynnDepartment of Community and Family Health, College of Public Health, University of South Florida, Tampa, FL, USAI am writing to comment on Kontomanolis et al’s recent article entitled “The social stigma of HIV-AIDS: society’s role”.1 Although I applaud the authors for writing about this important topic and I wholeheartedly agree that HIV-related stigma is devastating to women living with HIV, I want to point out that using stigmatizing language when writing an article about HIV-related stigma is counterproductive.View the original paper by Kontomanolis and colleagues.